Repurposing agricultural policies and support: Options to transform agriculture and food systems to better serve the health of people, economies, and the planet - Gautam, Madhur; Laborde Debucquet, David; Mamun, Abdullah; Martin, Will; Piñeiro, Valeria; Vos, Rob (World Bank, 2022)
The report finds that repurposing a portion of government spending on agriculture each year to develop and disseminate more emission-efficient technologies for crops and livestock could reduce overall emissions from agriculture by more than 40 percent. Meanwhile, millions of hectares of land could be restored to natural habitats. The economic payoffs to this type of repurposing would be large. Redirecting about $70 billion a year, equivalent to one percent of global agricultural output, would yield a net benefit of over $2 trillion in 20 years.